Is lipohypertrophy marely a cosmetic defect? The impact of lipohypertrophy on treatment and lives of patients with diabetes - a literature review - Graczyk, Alicja; Hajt, Michał; Grabowska, Natalia; Misiaszek, Dastin; Wolszczak, Anna; Motor, Jakub; Martynowska, Weronika; Ciecierski, Piotr (Quality in Sport, 2026)
Background: : Lipohipertrophy (LH) is a common complication of diabetes, regardless of its type, in which the tissue exposed to insuline lead to hypertrophy of adipocytes and fibrosis. Despite it looks like only a visual problem, it has many negative consequences, that pose a threat to patients' health, lives, and quality of life. Aim: In this article we would like to present the multiple dimensions affected by this complication, as well as the potential benefits associated with the treatment of LH. Methods: A narrative review was conducted using the medical databases PubMed, Google Scholar, and ScienceDirect, with a focus on the impact of insulin-induced LH on the health and daily functioning of patients with diabetes. Results: The following aspects were analyzed: the impact of LH on glycemic control, risks associated with glycemic variability, long-term complications, quality of life, effects on the management of comorbidities, mental health, and treatment-related costs. Each of these domains was found to be significantly impaired or complicated by the presence of LH. Furthermore, improvements in patient health outcomes were observed in cases where regression of LH lesions was achieved. Conclusion: The entirety of the reviewed literature indicates that LH constitutes a substantial clinical challenge. Early detection, prevention, and effective management are essential for improving disease control and enhancing the quality of life for patients with diabetes.